INNOVATION MANAGEMENT BIOTECHNOLOGY OF STARTER CULTURES - Prosekov A.Y.; Ostroumov L.A. (Техника и технология пищевых производств)
According to experts, one of the innovative directions of the development of food biotechnology is the development of biotechnological approaches to the production of probiotics, prebiotics, synbiotics, ferments and food ingredients, new strains of lactic acid and other technological microorganisms, microbial consortia with predetermined biological properties and optimized processing characteristics. The inclusion of polycomponent probiotic consortia - bacterial preparations from cultures of lactic acid bacteria - into foods can be the basis for the prevention of various diseases. Experts predict the start of production of probiotic products with proven efficiency in Russia by 2017 and their mass production by 2020. The use of lactic acid bacteria as starter cultures of direct application and having necessary range of features will improve the functional-and-technological and consumer properties of dairy products. The paper deals with the study of physiological-and -biochemical and commercially valuable properties of strains of lactic acid bacteria when creating combined starter cultures of direct inoculation with high proteolytic activity. It has been found that the lactic acid bacteria of Lactococcus lactis subspecies cremoris B 2276, Lactobacillus plantarum B 3242, Lactococcus lactis B 5946 and Leuconostoc mesenteroides subspecies mesenteroides B 8404 have high proteolytic activity contributing to the formation of low molecular weight peptides and free amino acids in milk and show high antagonistic activity against sanitary significant intestinal microorganisms (Staphylococcus aureus, Proteus vulgaris, Escherichia coli) . The results on the study of biocompatibility show the lack of inhibitory effect which allows their use in preparing the combined starter of direct inoculation.